Two kinds of lateral flow immunoassays based on multifunctional magnetic prussian blue nanoenzyme and colloidal gold for the detection of 38 β-agonists in swine urine and pork. (15th August 2023) - Liang, Jinxuan; Liu, Zhiwei; Fang, Yalin; Shen, Xing; Xu, Zhenlin; Lei, Hongtao; Huang, Xianhui; Li, Xiangmei
Highlights: A novel magnetic prussian blue nanoenzyme and colloidal gold were synthesized. Two kinds of lateral flow immunoassays were developed for detection of 38 β -agonists. The sensitivity of the developed assays were 200-fold higher than that of the reported methods. Abstract: Herein, novel multifunctional magnetic prussian blue nanoenzymes (MPBNs) and colloidal gold (CG) were synthesized and used to develop two kinds of lateral flow immunoassays (LFIAs) for the detection of 38 β -agonists. Since MPBNs has a unique three-in-one function of colorimetric magnetic catalytic activities, the signal intensity and coupling ratio are 2 and 8-fold higher than that of the CG. The cut-off values of the CG-LFIA and MPBNs-LFIA for swine urine and pork are 5/5 and 0.3/0.5 μg/kg, the limits of detection are 0.19/0.29 and 0.02/0.03 μg/kg, respectively. The sensitivity of MPBNs-LFIA is 10-fold higher than that of CG-LFIA, and up to 200-fold higher than that of the reported LFIAs. The recoveries of the LFIAs are 80.0%–116.7%, with coefficients of variation of 1.4%–14.3%. Our study proved that the MPBNs have more advantages than CG, and can offer a promising signal label for ultrasensitive immunoassay techniques.